BUSINESS PROSPECT OF THE TILAPIA HATCHERIES BY STANDARD OPERATING PROCEDURE APPLICATION OF GOOD HATCHERY PRACTICES (GHP) IN BANJAR REGENCY SOUTH KALIMANTAN - Rahmani, Fathur (The Journal is published by Graduate Programe of Lambung Mangkurat University, 2017)
This research aimed to (1) analyze the profit of the tilapia hatchery business in Banjar Regency with GHP application and comparing it with the profit before it applied GHP; and (2) to analyze the investment feasibility of the tilapia hatchery business with GHP application in Banjar Regency. This research was carried out in the Karang Intan District, Banjar Regency, South Kalimantan, with the community GHP certified hatchery units as the object. The collected data was the data that directly originated from observation results in the location of the research, and other supporting data, which related to the object of the research. The results of the research showed that by applying GHP, the tilapia hatchery business gave more profit than before applying it. By applying GHP, the tilapia hatchery business developed very profitably and feasible to be carried on. The result of investment feasibility analysis showed that the NPV was positive, the Net BCR was more than 1, the IRR was more than discounted rate, and the period of the return of investment was faster than the project period.